Jubileumi programok a 475 éves Debreceni Református Kollégium intézményeiben - Fekete, Károly (Gerundium, 2018)
ANNIVERSARY PROGRAMS IN THE INSTITUTES OF THE 475-YEAR-OLD REFORMED COLLEGE OF DEBRECEN. he Reformed College of Debrecen celebrated its 475th anniversary in 2013. he College is a unique and interesting institute of Hungarian school system. It is a national historical site, where the reformed heritage of the 16th century, the values of Puritanism of the 17th century, and the intellectual efervescence of the 18th century are commemorated. Anational historical site where the victims of the freedom ight for our independence in 1848–49 are kept alive and where the College’s mission to foster talent even during the turbulent times of the 20th century is remembered. Today teaching activities are present on all levels of public and higher education from the kindergarten to the university.